Clove as antioxidant additive in diesel–biodiesel fuel blends in diesel engines. Issue 4 (16th March 2019) - Jeyakumar, Nagarajan; Narayanasamy, Bose
ABSTRACT: Increased NOx emission from usage of biodiesel is a burning issue to be dealt with. Many techniques have been adopted to reduce NOx emissions from diesel engines. The present experimental study deals with the analysis of performance and emission characteristics of Cotton Seed oil biodiesel with the addition of natural antioxidant extract of clove. FTIR analysis characterized the antioxidant by the presence of hydroxyl groups denoted by the corresponding wave number. The oxidation stability of the test samples was determined in terms of induction period by means of Rancimat test. The induction periods of the test fuel samples B100, B20, B20+CL1000, and B20+CL2000 were found to be 2.20 h, 2.73 h, 10.19 h, and 11.12 h, respectively. Thus, the addition of Clove antioxidant increased the oxidation stability of the biodiesel. Results show that the addition of antioxidant to biodiesel blend has increased the Brake Thermal Efficiency to a maximum of 4.71% and decreased the Brake Specific Fuel Consumption to a maximum of 8.05% at full-load conditions compared to Cotton Seed biodiesel blend. The addition of Clove extract antioxidant at a concentration of 1000 ppm and 2000 ppm decreases the NOx emission by 23.03% and 26.7%, respectively, at full-load conditions. However, CO emissions increased by 1.12% and 4.49% with the addition of CL1000 and CL2000 to B20, respectively. Similarly, HC emissions increased by 4.19% and 7.35% by the addition of CL1000 and CL2000 to B20, respectively. The increase in smoke with the addition of CL1000 and CL2000 to B20 were 42.48% and 47.71%, respectively.